Discrete and Differential Equations in Applied Mathematics - Miroslava Ruzickova (Communications - Scientific letters of the University of Zilina, 2008)
In the contribution we map investigations performed in mathematics at the Faculty of Science in 2003–2007. Main directions developed at the faculty are described and some of the latest achievements are presented. We illustrate some results from control theory for discrete delayed equations, perturbed linear problems for discrete equations, results concerning the structure of solutions of delayed differential equations, results of orthogonal polynomials, and adescription of some numerical investigations in discrete least-squares and collocation methods for numerical solution of a boundary value and eigenvalue problems. Some of accompanying mathematical activities are mentioned as well.